2021
DOI: 10.1186/s12903-020-01349-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep bruxism is associated with vitamin D deficiency and low dietary calcium intake: a case-control study

Abstract: Background Sleep bruxism may result in deleterious effects including loss of tooth enamel, fracture of teeth or restorations, teeth hypersensitivity or pain, and headache. The aim was to study the link between sleep bruxism, low serum vitamin D, low consumption of dietary calcium, psychological symptoms, and frequent headache. Methods This case-controlled study included 50 individuals with sleep bruxism and 50 age and gender matched controls. 25-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Alkhatatbeh, M. J., [51] Case-control study 100 subjects Vitamin D levels were significantly lower in subjects with sleep bruxism.…”
Section: First Author and Year Type Of Study Sample Size Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkhatatbeh, M. J., [51] Case-control study 100 subjects Vitamin D levels were significantly lower in subjects with sleep bruxism.…”
Section: First Author and Year Type Of Study Sample Size Resultsmentioning
confidence: 99%
“…Bruxism is a rhythmic masticatory muscle activity, characterized by teeth grinding and clenching, which can occur during sleep or while awake [50].In 2021, Alkhatatbeh et al published a case-control study, investigating whether there is an association among the low intake of dietary calcium, low levels of vitamin D, headache, and psychological symptoms (such as anxiety and depression) and sleep bruxism. A total of 100 subjects were enrolled in this observational study, and the results showed that, compared with the control groups, the subjects with sleep bruxism had higher anxiety and depression rates, and their vitamin D levels were significantly lower [51].…”
Section: Vitamin D and Temporomandibular Disordersmentioning
confidence: 99%
“…The findings regarding age coincided with a study conducted in Jordan that showed the association between bruxism and vitamin D and calcium deficiency in the diet, which indicated that this behavior was not associated with the age of the participants. 32 Another study reported similar results when evaluating the level of work stress and factors asso-ciated with sleep bruxism in crew members of the Peruvian Air Force. 33 Likewise, a study that evaluated 600 children aged 4 to 12 years in Tehran suggested that there was correlation between bruxism and age.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies focusing on genetic factors also found two microRNAs (viz., miR‐15b‐5p and miR‐92b‐3p) that may modify OSA‐related depression 41 . On the other hand, compared with individuals without SB, SB patients were found to have higher scores of depression 42 . SB has long been known to be regulated centrally, and depression is considered a potential aetiology of SB 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, compared with depression, arousal is a more well‐recognised connecting factor between OSA and SB, which may better explain the association between OSA and SB at event level. A previous PSG study reported the temporal association between OSA events and SB events, and the authors hypothesized that the co‐activation of oropharyngeal muscles may maintain the patency of the airway but may lead to SB at the same time, suggesting a potential protective role of SB against airway obstruction 42 . There is increasing evidence that SB events that are time‐linked to OSA events are associated with OSA event‐related arousals rather than with OSA events per se 44 .…”
Section: Discussionmentioning
confidence: 99%